The Effect of Using English Short Stories Toward Students’ Ability in Reading Comprehension at the Seventh Grade in Junior High School No. 15 Jambi City - Lisa Andriyani; Wennyta Wennyta; Siti Aisyah (JELT: Journal of English Language Teaching, 2022)
This research aimed to find out the effect of using English short stories in reading comprehension toward students’ ability of junior high school No. 15 Jambi City. In order to achieve the objective of this research, the research design used quasi-experimental. This research took two classes, an experimental class and control class. VII B was experimental class that consist of 30 students were taught by using English short story, and VIII C was control class that consist of 30 students were taught by using non-English short story. This research used a test instrument, a reading test in the form of multiple-choice test with 20 items with options A, B, C, and D. The technique of data collection of this research used a test as a research instrument. The technique of data analysis of this research is calculation the students' score and analyzing the students' score using SPSS. The data was analyzed by T-test using SPSS for windows version 16.0. The difference. It is found that the value of sig was 0,004, at the significance level of 5% (0,05) and then 0,004 < 0,05. In this research, Ho (null hypothesis) is rejected because the value of Sig < a in significant degree. (0,004 < 0,05) and alternative hypothesis (Ha) is accepted if the value of Sig < a in significant degree (0,004 < 0,05).  The explanation above proved that there is an effect of using English short stories in reading comprehension toward students’ ability of junior high school No. 15 Jambi City